2014
DOI: 10.1128/jvi.02223-14
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Phenotypic Analysis of CD8 + T Cell Responses after Priming with Alphavirus Replicons and Homologous or Heterologous Booster Immunizations

Abstract: Alphavirus replicons are potent inducers of CD8؉ T cell responses and thus constitute an attractive vaccine vector platform for developing novel vaccines. However, the kinetics and memory phenotype of CD8 ؉ T cell responses induced by alphavirus replicons are not well characterized. Furthermore, little is known how priming with alphavirus replicons affects booster immune responses induced by other vaccine modalities. We demonstrate here that a single immunization with an alphavirus replicon, administered as vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 74 publications
0
34
1
Order By: Relevance
“…We recently developed a number of CHIKV vaccine candidates based on the La Reunion (LR-CHIKV) strain of East Central South African (ECSA) genotype. These were able to induce protective immunity against CHIKV infection in mice (8)(9)(10)(11). Here, we have evaluated the safety, immunogenicity, and efficacy of 3 of those candidates in nonhuman primates.…”
Section: Introductionmentioning
confidence: 99%
“…We recently developed a number of CHIKV vaccine candidates based on the La Reunion (LR-CHIKV) strain of East Central South African (ECSA) genotype. These were able to induce protective immunity against CHIKV infection in mice (8)(9)(10)(11). Here, we have evaluated the safety, immunogenicity, and efficacy of 3 of those candidates in nonhuman primates.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that weekly injection of replicon vaccines (before contraction of the CD8 + T cell response), results in lower memory responses. 18,25 Hence we could speculate that the frequent injections as well as the high dose could synergistically weaken the immune response. Immunization with 3.2 µg of pVAX resulted in the same tumor growth pattern as for non-vaccinated mice.…”
Section: Resultsmentioning
confidence: 99%
“…18 Moreover, dosages higher than 10 μg results in lower antigen-specific responses. 18,25 For this reason, we also evaluated the anti-tumor effect of DREP at doses lower than 10 μg. Using the same schedule after tumor inoculation, we immunized mice with 0.2 and 0.05 μg of DREP.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations